2020
DOI: 10.1029/2019jd031565
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound and Gravity Waves Over the Andes Observed by a Pressure Sensor on Board a Stratospheric Balloon

Abstract: The study of infrasound (acoustic) and gravity waves sources and propagation in the atmosphere of a planet gives us precious insight on atmosphere dynamics, climate, and even internal structure. The implementation of modern pressure sensors with high rate sampling on stratospheric balloons is improving their study. We analyzed the data from the National Aeronautics and Space Administration Ultra Long Duration Balloon mission (16 May to 30 June 2016). Here, we focus on the balloon's transit of the Andes Mountai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…After all, the planet we know best is Earth and so far, our approach of relying on physical rules that govern the Earth to predict what we might see on other planets has served us well, at least in the seismic realm. Several confirmed detections of the non-seismic sources mentioned above from stratospheric balloons are already extant in literature (see e.g., Lamb et al (2018) for thunderstorms, and Poler et al (2020) for mountain waves). Long-duration data collection from balloons can help in further expanding this catalog, so that patterns can begin to emerge that would allow independent association of infrasound signals to originating events.…”
Section: Looking Forward To Venus … and Looking Back At Earth?supporting
confidence: 58%
“…After all, the planet we know best is Earth and so far, our approach of relying on physical rules that govern the Earth to predict what we might see on other planets has served us well, at least in the seismic realm. Several confirmed detections of the non-seismic sources mentioned above from stratospheric balloons are already extant in literature (see e.g., Lamb et al (2018) for thunderstorms, and Poler et al (2020) for mountain waves). Long-duration data collection from balloons can help in further expanding this catalog, so that patterns can begin to emerge that would allow independent association of infrasound signals to originating events.…”
Section: Looking Forward To Venus … and Looking Back At Earth?supporting
confidence: 58%
“…The waveform characteristics of the detected events depended on the distance from the source terrain, as more distant mountain ranges apparently resulted in lower frequencies at the sensors than nearer sources. MAWs have also been measured by infrasound sensors on a balloon when crossing the southern Andes (Poler et al 2020 ). An example waveform recording and its associated spectrogram is shown in Fig.…”
Section: Infrasonic Sourcesmentioning
confidence: 99%
“…By placing infrasound microbarometers on a high altitude balloon, Bowman and Lees (2015) showed that airborne sensors were able to capture sound fields very different from that of the Earth's surface, and that background noise levels were very low when the instruments were properly protected against electromagnetic interference. A 19 days infrasound sensing mission on a long duration balloon in the southern hemisphere then captured hitherto unsampled acoustic radiation above the ocean microbarom source region (Bowman & Lees, 2018), thunderstorms (O. Lamb et al., 2018), and wind/mountain interactions (Poler et al., 2020). The balloon circled Antarctica, at one point crossing through a 7,000 km gap between ground infrasound stations.…”
Section: How (And Why) Infrasound Sensing Took To the Skymentioning
confidence: 99%
“…sensing mission on a long duration balloon in the southern hemisphere then captured hitherto unsampled acoustic radiation above the ocean microbarom source region , thunderstorms (O. Lamb et al, 2018), and wind/mountain interactions (Poler et al, 2020). The balloon circled Antarctica, at one point crossing through a 7,000 km gap between ground infrasound stations.…”
mentioning
confidence: 99%